2015
DOI: 10.3389/fpsyg.2015.01267
|View full text |Cite
|
Sign up to set email alerts
|

Reading is for girls!? The negative impact of preschool teachers' traditional gender role attitudes on boys' reading related motivation and skills

Abstract: According to gender stereotypes, reading is for girls. In this study, we investigated the role of preschool teachers in transmitting such gendered expectations. We suggest that boys are less motivated to read in preschool, and less competent in reading 1 year later in primary school, if their preschool teacher holds a traditional gender role attitude than if the teacher has egalitarian beliefs. In 135 independent dyads of a female preschool teacher (N = 135) and one boy (n = 65) or one girl (n = 70) we measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
54
1
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(66 citation statements)
references
References 63 publications
4
54
1
7
Order By: Relevance
“…By contrast, regarding reading skills in the Netherlands, Boerma et al (2015) found that teachers tend to perceive girls to be better at reading than boys. These results confirmed earlier findings in Germany by Wolter, Braun, and Hannover (2015), who also found a gender bias in teacher expectations of reading abilities: more positive expectations for girls than for boys. In summary, these findings suggest that teacher expectations are biased by gender; girls are identified as being better than boys in areas to do with "letters", and the reverse is true in areas involving "maths" or "sciences".…”
Section: The Influence Of Student and School Ses And Gender On Teachesupporting
confidence: 91%
“…By contrast, regarding reading skills in the Netherlands, Boerma et al (2015) found that teachers tend to perceive girls to be better at reading than boys. These results confirmed earlier findings in Germany by Wolter, Braun, and Hannover (2015), who also found a gender bias in teacher expectations of reading abilities: more positive expectations for girls than for boys. In summary, these findings suggest that teacher expectations are biased by gender; girls are identified as being better than boys in areas to do with "letters", and the reverse is true in areas involving "maths" or "sciences".…”
Section: The Influence Of Student and School Ses And Gender On Teachesupporting
confidence: 91%
“…However, the influence of another important socializer was not included in our study. Teachers have been found to hold negative stereotypes regarding boys’ reading competencies that impact on boys’ reading self‐concept and skills (Retelsdorf et al ., ; Wolter, Braun, & Hannover, ). The influence of teachers’ beliefs on students’ achievement is further not limited to their impact on students’ motivation and actual skills acquired, but additionally impacts on students’ grades (Jussim & Eccles, ).…”
Section: Discussionmentioning
confidence: 99%
“…As teachers' beliefs are thought to influence parents' beliefs concerning their child competencies more profoundly than vice versa (Simpkins et al, 2015), we concentrate on teachers' beliefs. In general, the important role of teachers' beliefs concerning children's ability self-concept formation has been underlined by many empirical studies (e.g., Keller, 2001;Herbert and Stipek, 2005;Wolter et al, 2015; for related research on the role of parents, see e.g., Tiedemann, 2000b;Tomasetto et al, 2015). For instance, teachers' belief that girls have superior reading skills than boys predicted a decline in boys' reading self-concept whereas girls' reading self-concept was unrelated (Retelsdorf et al, 2015).…”
Section: The Role Of Socializers' Beliefsmentioning
confidence: 99%